(untitled) (Sudurpaschim Spectrum, 2026)
Nepal, a multiethnic, multilingual, and multicultural nation, faces both unique opportunities and persistent challenges in managing its rich diversity. While the 2015 Constitution has introduced inclusive measures—such as the recognition of minority languages, reservation policies for marginalized groups, and the declaration of a secular state—practical implementation remains limited. Previous research has largely celebrated multiculturalism’s normative ideals but has paid insufficient attention to Nepal’s persistent caste hierarchies, linguistic dominance, and unequal citizenship practices. This study addresses this research gap by critically examining how multicultural policies operate in practice and whether they achieve intended social integration. Findings reveal that, despite constitutional provisions, discrimination, cultural favoritism, and inequities in citizenship and education continue to marginalize minority communities. Globalization and tourism further complicate cultural preservation. The study stresses that Nepal’s greatest challenge lies not in policy creation but in policy execution and social acceptance. It concludes that sustained dialogue, genuine meritocracy, and proactive engagement with minority voices are crucial for maintaining national integrity in an increasingly diverse society. These critical perspectives carry significant implications for policymakers aiming to foster peace, inclusion, and equitable development in multicultural states.